22. Plasticity of sensorimotor system induced by sustained pressure stimulation - Hok, Pavel; Hluštík, Petr; Kutín, Miroslav; Opavský, Jaroslav; Tüdös, Zbyněk; Kaňovský, Petr (Clinical neurophysiology, 2015)
The aim of this study was to assess functional changes occurring at central nervous system (CNS) in healthy volunteers after sustained pressure stimulation according to Vojta (Bauer et al., 1992), a physiotherapeutic method involving induction of a complex motor response, so called reflex locomotion. Although the therapy has been widely used in clinical practice, its underlying neurobiological basis remains a speculation. We hypothesize that the stimulation-driven response induces CNS plasticity at subcortical level detectable by functional magnetic resonance imaging (fMRI), possibly involving specific changes in task-related sensorimotor system activation as well as modulation of resting state networks. Two groups of healthy volunteers were included (17 females and 5 males in each group, mean age 24.5 and 24.7 respectively): Group A receiving stimulation at the Vojta right heel zone and Group B receiving control stimulation of the right ankle. All subjects underwent a single fMRI session using a 1.5T Siemens scanner, including 6 experimental runs employing 3 different conditions: rest (6min); dominant hand finger tapping alternating with rest (6min); intermittent pressure stimulation applied by an experienced therapist (10min). Both rest and finger tapping conditions were tested before and after two consecutive stimulation runs. Statistical analysis, including standard pre-processing, nuisance signal regression and group post hoc contrasts, was carried out using FEAT, and MELODIC followed by Dual Regression, parts of FSL (Jenkinson et al., 2012) 5.0. The resulting statistical maps were thresholded at corrected significance level p<0.05. In finger tapping task, diffuse activation decrease within sensorimotor system was observed in both groups. However, there was significant activation increase mainly in motor nuclei of left thalamus detected only in group A. Additionally, group A showed significant decrease of functional connectivity in the left superior parietal lobule within the bilateral sensorimotor resting-state network. Our findings provide evidence that stimulation according to Vojta is associated with specific and persistent changes of brain activation, as compared to the control stimulation. The observed changes could represent neurophysiological correlate of Vojta therapy and suggest an important role of subcortical structures. Supported by grant GACR 14–22572S.